2013
DOI: 10.1038/hr.2013.112
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of losartan and carvedilol on central hemodynamics in hypertensives: a prospective, randomized, open, blinded end point, multicenter study

Abstract: Renin-angiotensin system (RAS) blockers have shown clinical outcomes superior to those of the beta (β)-blocker atenolol, despite similar reductions in the peripheral blood pressure (BP), perhaps because of different impacts on central hemodynamics. However, few comparative studies of RAS blockers and newer vasodilating β-blockers have been performed. We compared the central hemodynamic effects of losartan and carvedilol in a prospective, randomized, open, blinded end point study. Of the 201 hypertensive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
0
14
0
2
Order By: Relevance
“…Se excluyeron cuatro estudios porque solo comunicaban los cambios agudos de PA inducidos por el tratamiento, [27][28][29][30] 5 debido a valores incompletos de PA central basales o después del tratamiento, 12,16,25,31,32 3 debido a los criterios de inclusión, 33-35 2 por duplicar otras publicaciones, 36,37 2 por ausencia de un grupo control 38,39 y 1 porque la determinación de PA se efectuó con un dispositivo no validado. 40 En total, se incluyeron 20 estudios en el análisis cuantitativo, cuyas principales características se comunican en la Tabla 1 y la Tabla S1 del Suplemento de datos solo en línea.…”
Section: Selección De Estudiosunclassified
See 2 more Smart Citations
“…Se excluyeron cuatro estudios porque solo comunicaban los cambios agudos de PA inducidos por el tratamiento, [27][28][29][30] 5 debido a valores incompletos de PA central basales o después del tratamiento, 12,16,25,31,32 3 debido a los criterios de inclusión, 33-35 2 por duplicar otras publicaciones, 36,37 2 por ausencia de un grupo control 38,39 y 1 porque la determinación de PA se efectuó con un dispositivo no validado. 40 En total, se incluyeron 20 estudios en el análisis cuantitativo, cuyas principales características se comunican en la Tabla 1 y la Tabla S1 del Suplemento de datos solo en línea.…”
Section: Selección De Estudiosunclassified
“…Four studies were excluded for reporting only acute treatment-induced BP changes, [27][28][29][30] 5 because of incomplete central BP values at baseline or after treatment, 12,16,25,31,32 3 because of the inclusion criteria, 33-35 2 for duplicating other publications, 36,37 2 for the absence of a control group, 38,39 and 1 because central BP assessment was performed with a nonvalidated device. 40 Overall, 20 studies were included in the study for quantitative analysis, and the main characteristics are reported in Table 1 and Table S1 in the online-only Data Supplement.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carvedilol has been shown to inhibit agonist binding at ␤ 1 -and ␤ 2 -ARs and also to block norepinephrine binding to ␣ 1 -ARs to reduce vasoconstriction (25,30,37). As a result, the hemodynamic effects of carvedilol are similar to those of renin-angiotensin system blockers and significantly greater than those of conven-tional ␤-AR antagonists such as atenolol (15,17). Furthermore, carvedilol has been shown to function as an inverse agonist by blocking G protein activation while stimulating ␤-arrestinassociated signaling pathways (14).…”
mentioning
confidence: 64%
“…Clinical evidence also suggests that these agents are more potent than conventional beta-blockers in reducing central systolic pressure [65,66,67], with recent studies suggesting that nebivolol is as effi cacious as ACEis, ARBs and aliskiren in this respect [56,57]. Likewise, among hypertensive patients, carvedilol and losartan reduce central pressure to a similar extent [68]. It can be assumed that a reduction of wave refl ections associated with the vasodilating properties of the newer beta-blockers may partly explain their benefi cial eff ects on central pressure.…”
Section: Do Some Drug Classes Have More Benefi Cial Effects On Centramentioning
confidence: 97%